Penerapan Problem Based Learning Dalam Pembelajaran Mengubah Teks Wawancara Menjadi Narasi Pada Siswa Kelas VII MTs Plus Darul Hufadz Jatinangor Kabupaten Sumedang - Ani Sri Mulyani; Farhana, Hana Rizki; Syahidah, Raihana Nurul; Rojak, Johan (Prodi PGMI STAI Sabili Bandung, 2022)
To overcome the lack of effectiveness and efficiency in the delivery of teaching materials by teachers. the teacher as an educator must always improve the quality of his professionalism by providing learning opportunities to students by involving students effectively in the learning process. In this study, the method used is an experimental method regarding the application of problem based learning in narrating interview texts for Class VII MTs students. Plus Darul Hufadz. The experiment in question is pre-experimental because in this study only one sample or no comparison sample was used. This PBL-based research concluded that the pretest showed various categories, namely 0% or none of the students were in the poor category, 17 or 77% of the students were in the sufficient category, and 5 or 23% of the students were in the good category. at the posttest or after being given treatment in the form of the application of the Problem Based Learning learning model showed a significant increase, namely students who were in the good category after being given treatment. There are 16 or 73% of students in the good category and 6 or 27% of students in the sufficient category. Learning to narrate interview texts through the Problem Based Learning learning model is proven to be able to improve students' abilities. it can be seen that there is a significant difference between the ability to narrate the interview text before and after the application of the PBL method to students.